Practical Strategies for Clinical Management of Bullying - Shetgiri, Rashmi (Springer, 2015)
This timely Brief offers up-to-date findings about bullying--from trends and outcomes to assessment and identification--and workable approaches to combat this social epidemic on multiple fronts. The book examines links between bullying and mental health issues, the complex dynamics between bully and bullied (especially since bullies themselves may be victimized by others) and new challenges presented by youth involvement in social media. Effects of whole-school interventions involving students, teachers, and administrators, on bullying and its consequences, are concisely presented. And clinicians have guidelines for coordinating with children, parents, schools and the community.